Investment decision making using a combined factor analysis and entropy-based topsis model - Hsu, Li-Chang (Journal of Business Economics and Management, 2013)
Traditionally, the return on assets and the return on equity are used as the criteria in the evaluation of financial performance, while risk considerations are ignored. Therefore, this study combined financial ratio variables and the RAROC (risk-adjusted rate of return on capital) as the evaluation criteria and developed a financial performance evaluation model. The proposed evaluation model combines factor analysis with entropy weight and the TOPSIS (technique for order performance by similarity to ideal solution) to evaluate the financial performance of Taiwan’s 50 listed opto-electronic companies. Finally, Spearman’s and Kendall’s rank correlations are used to verify that there is no significant difference between the 2007 and 2008 rankings of the companies. The empirical results show the financial performance rankings of the companies before and after the global financial turmoil. These findings not only help investors making investment decisions, but also can help managers make decisions to improve their company’s financial performance.